Primary acquired cicatrizing gastric outlet obstruction in children - Manish Pathak; Rahul Saxena; Hardik Patel; Arvind Sinha (Journal of Indian Association of Pediatric Surgeons, 2022)
Background: Gastric outlet obstruction (GOO) is a very rare condition in children, when infantile hypertrophic pyloric stenosis is excluded as a cause. Five cases of pediatric GOO were successfully managed at our institute. Materials and Methods: We retrospectively evaluated children with idiopathic GOO from 2009 to 2016. Medical records were reviewed for demographic data including age, sex, presenting symptoms, diagnostic investigations, treatment methods, complications, and long-term follow-up. Results: During 7 year period (2009–2016), 5 cases of GOO admitted to our hospital with a history of persistent vomiting. The vomiting used to occur 12–18 h after meal and vomitus contained foul-smelling undigested meal. There was no history of any caustic ingestion. Their age ranged from 2 to 10 years, with a median age of 6 years. Out of 5 cases, 2 were females and the rest were males. The diagnosis of idiopathic GOO was confirmed by history, clinical examination, contrast study, endoscopy, and endoscopic mucosal biopsy. The remarkable finding was the cicatrization causing stricture of the pyloric region in all cases. Out of 5 cases; we have done Heineke-Mikulicz pyloroplasty in 1 case, V-Y advancement antropyloroplasty in 2 cases and Kimura's Diamond-shaped Gastroduodenostomy in 2 cases. The length of the strictured segment determined the type of surgical procedure. All cases did well postoperatively with no mortality. Conclusions: Length of the stricture determines the procedure to be done. In long and narrow stricture V-Y advancement antropyloroplasty and in small stricture Kimura's diamond-shaped Gastroduodenostomy are better procedures to be done. Heineke-Mikulicz pyloroplasty should be avoided as it is difficult to suture transversely after vertical incision because of the presence of fibrosis in the strictured segment.